COVID-19: Threat or Opportunity? - Mozhgan Rivaz; Seyed Mojtaba Kazemi; Mina Mosallanezhad (Universidad de Antioquia, 2020)
The COVID-19 pandemic is spreading quickly. Despite scientists' best efforts all over the world, there is not a vaccine or definite treatment for it and the novel coronavirus remains a threat to humanity with far-reaching, and in many cases, irredeemable consequences for the economic, political, social-psychological , and cultural aspects of humans' lives.(1)The quick transmission and fatality of the disease, absence of herd immunity, lack of or inequitable distribution of resources, e.g. Personal Protective Equipment ( PPE), and the existing challenges in the implementation of social distancing result in a daily increase in the number of victims and, consequently, an ever-expanding workload in healthcare systems worldwide. Moreover, the increasing mortality and morbidity of COVID-19 and lack of hospital beds and ventilators have led to healthcare provider's exhaustion and burnout.(1,2) Healthcare providers, especially nurses are the most vulnerable group in the face of the current disaster. Unfortunately, In the world, many front-line experts have lost their lives.(3)